2020
DOI: 10.1177/0145561320906906
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Bovine Collagen Grafts for Repair of Tegmen Defects and Encephaloceles Via Middle Cranial Fossa Approach

Abstract: To evaluate the use of commercially available allogenic dural graft materials made of fetal bovine collagen, we present an analysis of our case series with use of autologous and allogenic graft materials. Patients who underwent surgical repair of a tegmen tympani defect associated with ipsilateral conductive hearing loss and cerebrospinal fluid (CSF) otorrhea using a middle cranial fossa (MCF) approach from 2004 to 2018 at Loyola University Medical Center were included. Resolution of CSF otorrhea, audiologic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…22 Patel et al reported outcomes with various repair strategies using an autograft, an allograft, or a combination of the two, with overall excellent outcomes pertaining to hearing improvement and resolution of CSF leak. 23 In both the combined ID/ED repair and ED-only repair patient cohorts, the majority of surgeries utilized autologous squamosal temporal bone from the craniotomy to cover the bony defects. However, there were important differences in the other allograft materials used for reconstruction between the two cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…22 Patel et al reported outcomes with various repair strategies using an autograft, an allograft, or a combination of the two, with overall excellent outcomes pertaining to hearing improvement and resolution of CSF leak. 23 In both the combined ID/ED repair and ED-only repair patient cohorts, the majority of surgeries utilized autologous squamosal temporal bone from the craniotomy to cover the bony defects. However, there were important differences in the other allograft materials used for reconstruction between the two cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing outcomes after MCF tegmen repair are excellent with no reported sensorineural hearing loss. Past studies report that the majority of patients have objective overall improvement in hearing; however, the underlying pathology is likely to affect hearing outcomes in 60 to 93% of cases (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%